2009
DOI: 10.1523/jneurosci.3485-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

Functional Recovery after Lesion of a Central Pattern Generator

Abstract: In cases of neuronal injury when regeneration is restricted, functional recovery can occur through reorganization of the remaining neural circuitry. We found an example of such recovery in the central pattern generator (CPG) for the escape swim of the mollusc Tritonia diomedea. The CPG neurons are bilaterally represented and each neuron projects an axon through one of two pedal commissures. Cutting the posterior pedal commissure [pedal nerve 6 (PdN6)] in the animal or in the isolated brain caused a deficit in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(70 citation statements)
references
References 59 publications
1
69
0
Order By: Relevance
“…After hemisection, sprouting of sensory afferents has been reported on the lesion side (Helgren and Goldberger 1993;Murray and Goldberger 1974), and several segmental reflexes have been shown to become asymmetric Malmsten 1983a, 1983b;Malmsten 1983;Muir et al 1998). Changes within the functional connectivity of the CPG following a lesion within the intrinsic circuitry have also been reported in mollusks, explaining recovery of escape behavior without the need for regeneration (Sakurai and Katz 2009). In addition, and in accordance with our results, several studies have previously shown asymmetric changes imprinted in the spinal circuitry that were revealed by a complete SCI Rossignol 2003a, 2003b;Frigon and Rossignol 2008;).…”
Section: Discussionmentioning
confidence: 96%
“…After hemisection, sprouting of sensory afferents has been reported on the lesion side (Helgren and Goldberger 1993;Murray and Goldberger 1974), and several segmental reflexes have been shown to become asymmetric Malmsten 1983a, 1983b;Malmsten 1983;Muir et al 1998). Changes within the functional connectivity of the CPG following a lesion within the intrinsic circuitry have also been reported in mollusks, explaining recovery of escape behavior without the need for regeneration (Sakurai and Katz 2009). In addition, and in accordance with our results, several studies have previously shown asymmetric changes imprinted in the spinal circuitry that were revealed by a complete SCI Rossignol 2003a, 2003b;Frigon and Rossignol 2008;).…”
Section: Discussionmentioning
confidence: 96%
“…The fast reversion of left/right asymmetries observed in trained cats suggests that changes have occurred in the functional connectivity of the central pattern generators (CPG) controlling left and right HLs. An elegant work in an invertebrate CPG also shows that a new balance between left and right sides can be established following a lesion of the swim CPG (Sakurai and Katz, 2009). The fast recovery of escape behavior was shown to result from changes in synaptic weighting rather than anatomical reorganization.…”
Section: Training-induced Recovery and Spinal Plasticitymentioning
confidence: 99%
“…The adaptations observed after hemisection appeared to be mainly maintained by remaining descending pathways, thus creating a new left/right balance within the spinal circuits. In addition, physiological changes in synaptic weighting can occur within the CPG itself and could account for the establishment of a new balance between left and right sides (Sakurai and Katz 2009). Investigations are in progress to study the impact of locomotor training during the same base period.…”
Section: Role Of Locomotor Training and Delay During The Interlesion mentioning
confidence: 99%